Impact of Brief Interactive Psycho-Education Intervention on Caregiver toward Family Care Burden for Schizophrenic Patients at Puskesmas Kasihan II, Bantul - Triatmi Dyah Wahyuning; Adi Heru Sutomo; Carla R. Marchira (Faculty of Medicine, Public Health, and Nursing, 2018)
Background: Schizophrenia is a chronic severe mental disorder which causes a substantial burden of care for family caregivers.Objective: This study aimed to identify the effect of a brief interactive psycho-education intervention on caregivers towards family care burden for schizophrenic patients.Method: This study was a quasi-experimental design with one control group. Data were obtained from a random sample of patients who came to Puskesmas Kasihan II (Community and Primary Health Care Center). The participants in this research were 68 caregivers, who were divided into treatment and control groups. Both groups were administered a pre and post-test with the Burden Assessment Schedule questionnaire early in the first week and in the end or fourth week. The treatment group received a brief interactive psycho-education of schizophrenic patient care over one week for 4 sessions, while the control group received the prescribed essential medicines as usual.Results: This study showed that the average scores of the pre-test for the two groups were not significantly different (p value 0.77), while the averages of the post-tests were significantly different (p value 0.001).Conclusion: It was concluded that a brief interactive psycho-education for caregivers of schizophrenic patients was effective to decrease family care burden.